Every autumn comes the bear - Arnosky, Jim. (New York : Putnam's, 1993)
Every autumn a bear shows up behind the farm, and goes through a series of routines before finding a den among the hilltop boulders where he sleeps all winter long.
Publisher's Weekly
Booklist
School Library Journal
3.4
K-3
Keywords: Bears -- Fiction; Hibernation -- Fiction; Bears -- Fiction; Animals -- Hibernation -- Fiction